(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the chemical profile of the methanol extract (EMA-Met) from the leaves of Mabea angustifolia Spruce ex Benth., its biological and describe its morphoanatomy. M. angustifolia leaves were collected in the municipality of Itacoatiara, Amazonas, Brazil. After, they were dried, ground and subjected to extraction with solvents in increasing order of polarity. The EMA-Met extract was submitted to mass spectrometry analysis (APCI-MS) and evaluated by phytochemical screening. The biological action of the extracts was tested on Candida albicans (CP Robin) Berkhout 1923, Candida parapsilosis (Ashford) Langeron & Talice 1932 and on Salmonella Lignieres 1900 spp., Escherichia coli (Migula 1895) and Staphylococcus aureus Rosenbach 1884 bacteria. The morphoanatomical analysis of the leaves identified characteristics of diagnostic value for the species, such as leaf shape and margin, number and position of nectaries and colleters, branched tector trichomes and papillose cells on the abaxial surface of the epidermis. The phytochemical analysis revealed the presence of saponins, condensed tannins, phenols and flavonoids. The analysis by APCI-MS allowed the identification flavonoids of recognized biological activity in the literature, being two O-glycosides of quercetin, 3-O-α-L-arabinopirasil quercetin and quercetin-3-O-glucuronide, in addition to quercetin and myricetin-3-O-ramanoside. The extract solution at a concentration of 10 mg/mL inhibited E. coli, with an average halo diameter of 5 mm, the inhibition halo for C. albicans presented a diameter mean of 15 mm and for C. parapsilosis it was 16 mm. The results are promising, showing the antimicrobial potential of M. angustifolia.